Carbon-coated nickel foam for hypochlorous acid sensor - Sanjaya, Afiten Rahmin; Riyanto, Hanzhola Gusman; Rahmawati, Isnaini; Putri, Yulia Mariana Tesa Ayudia; Nurhalimah, Dede; Saepudin, Endang; Tesla, Yudistira; Krisnandi, Yuni Krisyuningsih (Environmental and Materials, 2023)
The electrochemical detection method of hypochlorous acid (HOCl) using carbon foam electrodes have been successfully developed. The carbon foam was prepared from carbon-coated nickel foam which is synthesized using a hydrothermal-carbonization method. SEM characterization indicated that the optimum synthesis of carbon-coated nickel foam has been achieved on the 4th layer coating process with an expected spherical structure, while characterization using FTIR and Raman spectroscopy confirmed the formation of graphitic material with D band and G band characteristics. An electroactive surface area of ​​0.0236 cm2 was achieved. Cyclic voltammetry of HOCl in 0.1 M phosphate buffer solution pH 6.0 showed the best current response for HOCl reduction occurs at a potential of -0.3 V (vs. Ag/AgCl). Further detection of HOCl using amperometry technique in the concentration range of 2-200 μg/mL showed good linearity with sensitivity of 9.112 mA/µg/L and an estimated detection limit of 1.96 µg/mL. Good repetition is indicated by the RSD value of 2.499 % (n=5). This developed sensor also showed good selectivity in the presence of interference compounds, such as FeCl2 and CuSO4. Besides, the determination of HOCl in tap water has been successfully conducted and generated a comparable result with the UV-VIS method (3.30 µg/mL hypochlorite). The results indicated that the developed sensor is promising for the detection of HOCl in environmental applications.